Academic Motivation and its Relationship with Academic Performance in Graduate Students: An Analysis of Homogeneity, Rank Restriction and the Ceiling Effect - Avila Colchao , Katia María (2025)
This study was conducted with the primary aim of establishing the correlation between academic motivation and academic performance in students enrolled in the Master's Program in University Teaching at the Faculty of Education of a public educational institution during the 2022 academic year. The research focuses on a crucial issue in contemporary higher education: the validation of traditional performance prediction models in highly specialized and homogeneous sample settings. Theoretically grounded in Self-Determination Theory (SDT) proposed by Ryan and Deci, the study explores the interaction between the intrinsic and extrinsic dimensions of motivation and academic performance metrics in a population of graduate students. The methodology employed follows a quantitative approach with a correlational scope, adopting a non-experimental, cross-sectional design. A group of 31 students, predominantly young adults and working professionals, participated. Data collection was carried out through a standardized questionnaire to quantify motivation and a review of official performance records. The statistical manipulation, carried out using SPSS v.25, included descriptive analyses, Shapiro-Wilk normality tests, and the calculation of Pearson's correlation coefficient. The results revealed a highly motivated student profile, with 64.5% falling into the "very high" motivation category and 35.5% into the "medium" category, with no instances of low motivation. Similarly, academic performance showed a high mean of 16.94 out of 20, with a low standard deviation (1.569), suggesting the presence of a "ceiling effect" and "range restriction." The inferential analysis yielded a Pearson correlation coefficient of r = 0.077 with a two-tailed significance of p = 0.682, leading to the acceptance of the null hypothesis of independence between the variables. The conclusions suggest that the lack of correlation does not refute the importance of motivation, but rather reflects statistical phenomena characteristic of select groups where variance is minimal. It discusses how motivation in postgraduate studies acts as a (constant) retention requirement rather than a differential predictor of performance, aligning with recent findings from the international literature that report decreasing correlations in hybrid and advanced learning environments.